Cell Wall Anchoring of the Campylobacter Antigens to Lactococcus lactis - Kobierecka, Patrycja A.; Olech, Barbara; Książek, Monika; Derlatka, Katarzyna; Adamska, Iwona; Majewski, Paweł M.; Jagusztyn-Krynicka, Elżbieta K.; Wyszyńska, Agnieszka K. (Frontiers in Microbiology, 2016)
Campylobacter jejuni is the most frequent cause of human food-borne gastroenteritis and chicken meat is the main source of infection. Recent studies showed that broiler chicken immunization against Campylobacter should be the most efficient way to lower the number of human infections by this pathogen. Induction of the mucosal immune system after oral antigen administration should provide protective immunity to chickens. In this work we tested the usefulness of Lactococcus lactis, the most extensively studied lactic acid bacterium, as a delivery vector for Campylobacter antigens. First we constructed hybrid protein – CjaA antigen presenting CjaD peptide epitopes on its surface. We showed that specific rabbit anti-rCjaAD serum reacted strongly with both CjaA and CjaD produced by a wild type Campylobacter jejuni strain. Next, rCjaAD and CjaA were fused to the C-terminus of the L. lactis YndF containing the LPTXG motif. The genes expressing these proteins were transcribed under control of the L. lactis Usp45 promoter and their products contain the Usp45 signal sequences. This strategy ensures a cell surface location of both analysed proteins, which was confirmed by immunofluorescence assay. In order to evaluate the impact of antigen location on vaccine prototype efficacy, a L. lactis strain producing cytoplasm-located rCjaAD was also generated. Animal experiments showed a decrease of Campylobacter cecal load in vaccinated birds as compared with the control group and showed that the L. lactis harboring the surface-exposed rCjaAD antigen afforded greater protection than the L. lactis producing cytoplasm-located rCjaAD. To the best of our knowledge, this is the first attempt to employ LAB (Lactic Acid Bacteria) strains as a mucosal delivery vehicle for chicken immunization. Although the observed reduction of chicken colonization by Campylobacter resulting from vaccination was rather moderate, the experiments showed that LAB strains can be considered as an alternative vector to deliver heterologous antigens to the bird immune system. Additionally, the analysis of the structure and immunogenicity of the generated rCjaAD hybrid protein showed that the CjaA antigen can be considered as a starting point to construct multiepitope anti-Campylobacter vaccines.